2019
DOI: 10.1186/s40662-019-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Associated risk factors in the early stage of diabetic retinopathy

Abstract: Background To investigate the retinal capillary density (RCD) of the macula using optical coherence tomography angiography (OCT-A) in type 2 diabetic patients and to further determine the association with risk factors. Methods A total of 212 eyes from 212 subjects were recruited; subjects included diabetics with no retinopathy (NDR, n = 90 eyes), diabetics with mild retinopathy DR (MDR, n = 36 eyes), and healthy part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…In addition, the mean T2DM lastingness at 38-months follow-up was 15 (3) years in −DR patients vs. 22 (5) years for the +DR patients. Nevertheless, additional factors also play critical roles in managing DR at any stage [1][2][3][4][5][6]19,[26][27][28], with a special interest in diabetics without clinically detectable retinopathy and those suffering from the early DR stage [37,38]. When corrected, these data for multiple testing, significantly lowered SLC23A2 gene expression (fold change) in the T2DM vs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the mean T2DM lastingness at 38-months follow-up was 15 (3) years in −DR patients vs. 22 (5) years for the +DR patients. Nevertheless, additional factors also play critical roles in managing DR at any stage [1][2][3][4][5][6]19,[26][27][28], with a special interest in diabetics without clinically detectable retinopathy and those suffering from the early DR stage [37,38]. When corrected, these data for multiple testing, significantly lowered SLC23A2 gene expression (fold change) in the T2DM vs.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical viewpoint, retinal microvascular changes found in the NPDR eyes are related to basement membranes thickening, pericyte loss, capillary occlusion, and microaneurysms, that can progress towards ischemia, macular edema, and neovascularization [ 4 , 5 , 19 , 36 , 37 , 38 ]. In this context, image analysis of retinal lesions can provide qualitative and quantitative data to accurately diagnosing and grading DR. Our data suggest relatively lower rates of progression of DR in our cohort during the 38-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hussain et al [15] show that the risk of diabetic retinopathy was higher for a male patient and a patient with age ≥ 49 years. Tan et al [18] showed that for a patient with mild DR, older age was associated with lower retinal capillary density, while the result in [31] reveal that sex is not a risk factor for being diabetic retinopathy, but they identified age as a strong predictor of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Ethiopia reported that, gender, haemoglobin a1c (HbA1c) and hypertension are predictive risk factors of diabetic retinopathy [17]. Some studies have also revealed that the odds of diabetic retinopathy is higher for a patient with higher HbA1c [4,12,15,18], longer duration of diabetes [5,12] and hypertensive patients [4,5,17]. A study based on data from a meta-analysis of seven cohort studies reported that insulin treatment has significant association with diabetic retinopathy in patients with type II diabetes mellitus [13].…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of DR varies from 10% to 61% in people with DM in different countries [5]. However, research has shown that reasonable intervention and treatment of DR in the early stage can achieve good results in preventing the development of the disease and significantly reduce the blindness rate [6][7][8].…”
Section: Introductionmentioning
confidence: 99%